If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x+6)/3=3x-5
We move all terms to the left:
2(x+6)/3-(3x-5)=0
We get rid of parentheses
2(x+6)/3-3x+5=0
We multiply all the terms by the denominator
2(x+6)-3x*3+5*3=0
We add all the numbers together, and all the variables
2(x+6)-3x*3+15=0
We multiply parentheses
2x-3x*3+12+15=0
Wy multiply elements
2x-9x+12+15=0
We add all the numbers together, and all the variables
-7x+27=0
We move all terms containing x to the left, all other terms to the right
-7x=-27
x=-27/-7
x=3+6/7
| 3/5w=-12 | | 7z-z=-2+4z-1-1 | | 1/4p=6 | | 5m-20=3m-11 | | 4s^2=9s+28 | | -3t+-15+4t+2=8 | | b-35/6=45/12 | | 110-(7x+8)=7(x+6)+x | | -25=-5/6v | | 394x+6)=-11+5 | | 1/2x+15=x | | 31/2xx=60 | | 8x-3(4-x)=76 | | F(x)=12x^2-25x-7 | | x+13/14=5/6 | | 5(3-2x)=3(2x+4) | | 1/2w=16 | | 2+6d=6+3D | | 4K+5/k+6=3 | | 16x+(-9)=-18+13x | | x+15+3x+17=90 | | -9/5=-2/3y-1/2 | | 13(x+1)-4x=3(3x+3)-15 | | 3(-5x)+9=13 | | -2(x)-9=-25 | | 3m-19=2m-8 | | 3(-5x)+9=14 | | 2/5h+-7=12/5h-2h+3 | | 3/2(6x+12)=24 | | 2x+6-5x+5=-28 | | C=22(3.14)r | | 2/3(x-3)+1/2x=5 |